A Guide to Social Science Research - Rwegoshora, Hossea (Dar es Salaam Mkuki na Nyonta, 2014)
Conducting social research requires an understanding of the general theories and principles of social science research. Such knowledge is essential for both social science students and all those undertaking research, evaluating, and designing different intervention strategies to existing social problems.
Keywords: Social Science